LAW AND ETHICS IN THE BUSINESS ENVIRONMENT - Halbert, Terry; Ingulli, Elaine (Cengage Learning legal studies in business academic series, 2018)
This edition dives into current controversies and makes classroom discussion with your instructor and peers come alive. Content prompts you to carefully consider recent, important court cases, while readings challenge you to think critically about contemporary legal and ethical dilemmas. Interactive assignments, such as role play, mock trials, and negotiation exercises, sharpen your ability to tackle tough problems and communicate effectively.